An evaluation of expansion equations for fluidized solid-liquid systems - SOYER, ELİF; AKGİRAY, ÖMER (IWA PUBLISHING, 2006)
Numerous equations can be found in the literature for the prediction of bed expansion during liquid-solid fluidization. There is no general agreement regarding which equation is the most fluidization experiments have been carried out with plastic and glass accurate. In this work, fluidization experiments have been carried out with plastic and glass spheres of 11 different sizes, varying from 1.11 mm to 6.01 mm. Water was used as the fluidizing medium in all the experiments. widely used correlations are compared and evaluated using the data collected in this work and certain long-standing data from the literature. A new equation with a simple and meaningful form is developed for the prediction of bed expansion in liquid fluidized beds of spheres. The proposed correlation is based on an extension of the fixed-bed friction factor concept to fluidized beds. The new equation has a number of advantages such as a wider operating range, improved accuracy, simple and continuous form, and a fundamental basis.
Keywords: bed expansion; filter backwash; fluidization; liquid-solid systems; porosity; PARTICULATE FLUIDIZATION; SEDIMENTATION; SPHERES; VOIDAGE; BEDS